Assessment of Birth Weight Parameters in Sverdlovsk Region: Preliminary Results - S. R. Belomestnov; T. V. Сhumarnaya; O. Yu. Sevostyanova; A. M. Ksenofontov; N. O. Аnkudinov; T. M. Isakova (Фундаментальная и клиническая медицина, 2024)
Aim. To define median and large-for-gestational-age birth weight in Sverdlovsk Region and to compare them with the results of a population study conducted in Central Europe.Materials and Methods. We conducted a retrospective analysis of 41,745 women. Inclusion criteria were singleton, full-term pregnancy, absence of fetal malformations, and delivery in a licensed medical organization. Exclusion criteria were multiple pregnancy, signs of chromosomal abnormalities during the antenatal development, congenital malformations, and incomplete examination according to the standard used for normal pregnancy. The results were compared with a similar study carried out in Central Europe.Results. The median weight of newborns at 37, 38, 39, 40, and 41 weeks was 3010, 3180, 3350, 3490, and 3600 g, respectively. “Large for gestational age” (above the 90th percentile) weight at 37, 38, 39, 40, and 41 weeks was 3550, 3720, 3900, 4020, and 4150 g, respectively. These parameters were significantly lower than those in Central Europe. Reproductive age, parity, and metabolic disorders were significant population determinants of birth weight.Conclusion. Birth weight parameters in Sverdlovsk Region differ from those in Central Europe, requiring further research. These data might be used for the correct assessment of the newborns and for development of a territorial strategy for the prevention of fetal growth disorders.